dirāsah li-maǧmū’ah dumā muktašafah min tall Muḥammad (Baġdād) li-sanah 1981 - al-Ḫayyāṭ, ’Adībah ’Alam al-Dīn
Study of a Collection of Figurines Discovered at Tell Muhammad (Baghdad) in 1981; ersch. 1987.